2022
DOI: 10.3389/fmicb.2022.820833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacterial Resistance of Escherichia coli From Swine in Large-Scale Pig Farms in Beijing

Abstract: With widespread use of antibiotics in the aquaculture industry, bacterial resistance has recently attracted increasing attention. Continuous emergence of multi-resistant bacteria has greatly threatened human and animal health, as well as the quality and safety of livestock products. To control bacterial resistance, the effect of bacterial resistance needs to be well understood. The purpose of this study was to explore the factors influencing Escherichia coli (E. coli) drug resistance in large-scale pig farms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Our results on the prevalence of AMR bacteria are consistent with ndings from previous studies carried at environmental level (33,34) or by faecal samplings (35)(36)(37). Our results highlight a relatively common occurrence of resistance against common antimicrobials (38), such as tetracycline, chloramphenicol, and trimethoprim/sulfamethoxazole, while resistance to last-resort antimicrobials, such as colistin, broadspectrum cephalosporins and carbapenems is less frequent.…”
Section: Discussionsupporting
confidence: 90%
“…Our results on the prevalence of AMR bacteria are consistent with ndings from previous studies carried at environmental level (33,34) or by faecal samplings (35)(36)(37). Our results highlight a relatively common occurrence of resistance against common antimicrobials (38), such as tetracycline, chloramphenicol, and trimethoprim/sulfamethoxazole, while resistance to last-resort antimicrobials, such as colistin, broadspectrum cephalosporins and carbapenems is less frequent.…”
Section: Discussionsupporting
confidence: 90%
“…The wide use of antibiotics has consequences, and there is a global concern in increasing antibiotic resistance. It has been reported that there is a high level of antibiotic resistance in porcine E. coli isolates from China [ 468 , 469 , 470 , 471 , 472 , 473 ]. Antibiotic resistance in E. coli is also prevalent on pork farms across Europe, including Spain [ 455 , 474 ], and other pork exporting countries such as Denmark, France, Italy, and Sweden are also found to be multi-drug resistant to antibiotics such as ampicillin, streptomycin, sulphonamide, tetracycline, and trimethoprim [ 475 ].…”
Section: Pathogenic E Coli Of Importance To Animal...mentioning
confidence: 99%
“…It is documented that most of the bacteria contaminated in fresh boar semen are E. coli [1-3,6], which show resistance to amoxicillin and ceftriaxone, whereas E. coli isolated from pig rectal and nasal swabs are resistant to tetracyclines, penicillin, and chloramphenicol [6,28]. Since antibiotic-resistant genes can spread to the surrounding environments of pig farms and also to humans, E. coli that is resistant to antibiotics on a pig farm remains a risk factor to public health and pig production [29].…”
Section: Discussionmentioning
confidence: 99%